2014
DOI: 10.1590/0001-3765201420130164
|View full text |Cite
|
Sign up to set email alerts
|

Re-induction of desiccation tolerance after germination of Cedrela fissilis Vell. seeds

Abstract: This work aimed to characterize the re-induction of desiccation tolerance (DT) in germinated seeds, using polyethylene glycol (PEG 8000). Cell changes were investigated through cytological assays (cell viability and transmission electronic microscopy) as well as DNA integrity during loss and re-establishment of DT. The loss of DT was characterized by drying germinated seeds with different radicle lengths (1, 2, 3, 4 and 5 mm) in silica gel, decreasing the moisture content to ten percentage points intervals, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 37 publications
2
21
0
Order By: Relevance
“…Similar results were observed for Glycine max (Senaratna and Mckersie, 1983). These results suggested that the loss of desiccation tolerance at the end of the germination process (radicle protrusion) was a norm, prompting the researches to test desiccation tolerance only in germinated seeds (Masetto et al, 2014(Masetto et al, , 2015Maia et al, 2016). Those studies ignored the possibility that the total loss may occur before Loss of desiccation tolerance in seeds... radicle protrusion, as it was observed in the present study for sucupira, pau-jacaré, and pau-ferro seeds, in which the loss of desiccation tolerance commenced already at the beginning of germination.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Similar results were observed for Glycine max (Senaratna and Mckersie, 1983). These results suggested that the loss of desiccation tolerance at the end of the germination process (radicle protrusion) was a norm, prompting the researches to test desiccation tolerance only in germinated seeds (Masetto et al, 2014(Masetto et al, , 2015Maia et al, 2016). Those studies ignored the possibility that the total loss may occur before Loss of desiccation tolerance in seeds... radicle protrusion, as it was observed in the present study for sucupira, pau-jacaré, and pau-ferro seeds, in which the loss of desiccation tolerance commenced already at the beginning of germination.…”
Section: Discussionsupporting
confidence: 75%
“…Those studies have been diverse, ranging from physiological and structural characterizations (Reisdorph and Koster, 1999;Guimarães et al, 2011;Pereira et al, 2014) to molecular and ecological analysis (Maia et al, 2011;Costa et al, 2016;Guimarães et al, 2016;Marques et al, 2017). Furthermore, desiccation tolerance reestablishment studies have been carried out to reactivate the mechanisms lost during the germination process (Buitink et al, 2003;Faria et al, 2005;Vieira et al, 2010;Maia et al, 2011;Masetto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that for seeds from forest species the period of loss of desiccation tolerance is variable. Masetto et al (2014) observed that Sesbania virgata seeds become intolerant to desiccation when protruded radicle reaches 2 mm while Cedrela fissilis did not tolerate desiccation in any radicle length. In studies with Copaifera langsdorffii seeds, Pereira et al (2014) verified that desiccation tolerance loss began at the end of the stage I and it was complete by the middle of stage II of germination.…”
Section: Imbibition Curve and Imbibition And Desiccation Tolerance Lossmentioning
confidence: 95%
“…Findings concerning the loss of desiccation tolerance during the seeds germination have already been reported in germinated seeds of Medicago truncatula (Buitink et al, 2003;Faria et al, 2005), Tabebuia impetiginosa (Vieira et al, 2010) and Cedrela fissilis (Masetto et al, 2014), where DT could be re-established applying a mild osmotic shock with polyethylene glycol. Mature seeds of S. virgata are desiccation tolerant (survive the loss of most of their water content), but they become desiccation sensitive while progressing to germination.…”
Section: Figure 1 Epifluorescence Micrographs Of Tunel Assays Performentioning
confidence: 77%